La capacocha del volcán Sara Sara: descripción y análisis de los objetos ofrendados y del contexto ritual - Bachraty, Dagmar (Pontificia Universidad Católica del Perú, 2025)
This report analyses the sacrificial context of the young female found in 1996 at the Sara Sara volcano in Ayacucho. The ensuing discussion, held from an ethnohistorical and archaeological perspective, shows the potential presence of a hierarchy among the capacochas, and also perhaps brings us closer, for the first time, to the function of this human sacrifice. This allows us to envision the individuality of the assemblage of ritual goods, which was directly connected with the message deployed within the Inca systems of power—in this specific case one of a propitiatory and agrarian nature—.

Este reporte analiza el contexto sacrificial de la joven encontrada en 1996 en el volcán Sara Sara, Ayacucho. La discusión, desde una perspectiva etnohistórica y arqueológica, revela la posible existencia de una jerarquía de capacochas, además de aproximarnos, por primera vez, a una posible función de este sacrificio humano. Ello permite visibilizar la individualidad del ajuar ritual, directamente vinculado con el mensaje desplegado dentro de los sistemas de poder incas. En este caso particular, de índole propiciatorio y agrario.
The capacocha of the Sara Sara volcano: description and analysis of the objects offered and the ritual context
Keywords: Sara Sara capacocha; Female attire; Maize; Female figurines; Grave goods; Capacocha del Sara Sara; Vestimenta femenina; Maíz; Figurinas femeninas; Ajuar funerario; https://purl.org/pe-repo/ocde/ford#6.01.02